2010
DOI: 10.1136/bjo.2009.174243
|View full text |Cite
|
Sign up to set email alerts
|

Is ranibizumab effective in stopping the loss of vision for choroidal neovascularisation in pathologic myopia? A long-term follow-up study

Abstract: Ranibizumab was an effective treatment for stabilising and improving vision with a low number of injections in 92.5% of patients with myopic CNV in a long-term follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
22
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 26 publications
(29 reference statements)
5
22
0
1
Order By: Relevance
“…Comparative observations of indocyanine-green angiography (ICGA) and FFA have shown that the two techniques have a discovery rate of lacquer crack-like lesions of 89 and 38%, respectively, indicating that ICGA can detect these lesions more effectively than can FFA (8). In the present study, lacquer cracks were detected in 40 out of 61 eyes (65.6%) with pathological myopia-induced macular CNV.…”
Section: Discussionsupporting
confidence: 43%
See 3 more Smart Citations
“…Comparative observations of indocyanine-green angiography (ICGA) and FFA have shown that the two techniques have a discovery rate of lacquer crack-like lesions of 89 and 38%, respectively, indicating that ICGA can detect these lesions more effectively than can FFA (8). In the present study, lacquer cracks were detected in 40 out of 61 eyes (65.6%) with pathological myopia-induced macular CNV.…”
Section: Discussionsupporting
confidence: 43%
“…Figurska and Stankiewicz (19) reported an Early Treatment Diabetic Retinopathy Study (ETDRS) visual acuity improvement of two lines in a 55-year-old patient who received two intravitreal injections of ranibizumab; furthermore, the ETDRS visual acuity was improved by three lines in another 25-year-old patient who received three intravitreal ranibizumab injections. A similar study (8) reported that the average number of intravitreal ranibizumab injections required to treat pathological myopia-induced macular CNV was 2.2, and the average BCVAs were 0.01 (prior to the treatment) and 0.30 (subsequent to the treatment). In the present study, the average number of injections was 1.97, and the average BCVAs were 0.02±0.01 and 0.30±0.03 prior to and subsequent to treatment, respectively.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…6,[8][9][10][11][12] The mean final VA in patients treated with anti-VEGF drugs reported in the literature ranges from 0.23 to 0.55 (Table 2). [6][7][8][9][10][11][12][31][32][33][34][35][36] More importantly, in studies which have compared anti-VEGF with PDT treatment for myopic CNV, patients treated with anti-VEGF generally achieved better visual outcomes compared with the group treated with PDT. 7,24,25 It is important to note, however, that in these studies, patients…”
Section: Discussionmentioning
confidence: 99%